2008
DOI: 10.1227/01.neu.0000317389.83808.16
|View full text |Cite
|
Sign up to set email alerts
|

The Translaminar Approach to Lumbar Disc Herniations Impinging the Exiting Root

Abstract: The translaminar approach is recommended in disc herniations encroaching the exiting root, as an alternative to the conventional interlaminar route.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
33
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(37 citation statements)
references
References 5 publications
4
33
0
Order By: Relevance
“…Bernucci and Giovanelli demonstrated a microscopic technique for the translaminar approach in 2007 (10), and Papavero et al described the usefulness of this approach the following year (11). The advantage of this technique is that it does not damage the facet joint and flavectomy is not necessary; therefore, it has been suggested that iatrogenic instability may be avoided.…”
Section: Discussionmentioning
confidence: 99%
“…Bernucci and Giovanelli demonstrated a microscopic technique for the translaminar approach in 2007 (10), and Papavero et al described the usefulness of this approach the following year (11). The advantage of this technique is that it does not damage the facet joint and flavectomy is not necessary; therefore, it has been suggested that iatrogenic instability may be avoided.…”
Section: Discussionmentioning
confidence: 99%
“…Associated pain has been described as particularly severe, which is believed to be related to direct pressure on the dorsal root ganglion [16]. The optimal approach to the pre-and intraforaminal lumbar region has been the subject of many studies [7][8][9]11,12,17]. Initially preferred by most surgeons, the standard interlaminar route by Caspar et al [10,18] proved to be rather unsuitable since nerve root exposure often required additional facetectomy or hemilaminectomy [4,19,20].…”
Section: Anatomical and Technical Considerationsmentioning
confidence: 99%
“…Partly unroofing the posterior wall of the foraminal compartment, this technique reduces bone damage and allows exposure of the medial and lateral part of the foramen [8,12,17]. Nevertheless, the pars interarticularis, which serves as the entry point in Di Lorenzo's approach [8], is one of the most fragile parts of the lumbar spine [24] and as Ivanov et al [25] recently demonstrated, the risk of stress fracture increases significantly when removing its lateral half.…”
Section: Anatomical and Technical Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…This strategy harbours a potential risk for relevant destruction of the facet joint complex [3] and postsurgical instability could be the consequence. For preserving the pars interarticularis and the facet joint a limited approach through the hemilamina is possible, which should be more direct and less destructive [1,2,5,8,10]. However, studies concerning biomechanical aspects, radiological sequale and clinical outcome comparing the translaminar and interlaminar approach do not exist to date.…”
Section: Introduction and Relevant Surgical Anatomymentioning
confidence: 99%